Computer Vision and Graphics International Conference, ICCVG 2012, Warsaw, Poland, September 24-26, 2012. Proceedings - Bolc, Leonard; Tadeusiewicz, Ryszard; Chmielewski, Leszek J.; Wojciechowski, Konrad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International Conference on Computer Vision and Graphics, ICCVG 2012, held in Warsaw, Poland, in September 2012. The 89 revised full papers presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections on computer graphics, computer vision and visual surveillance.
computer graphics -- computer vision -- visual surveillance.
Keywords: Computer science; Computer software; Artificial intelligence; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Graphics; Pattern Recognition; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics).